Evaluation of Bipolar Disorder in Several Recurrences over the Time Using Generalized Estimating Equations - Payam Amini; Roya Najafi-Vosough; Ali Ghaleiha; hossein mahjub (Iranian Journal of Psychiatry, 2017)
Objective: Bipolar disorder is characterized by periods of manic, depression, or mixed episodes. The purpose of this study was to assess the development of bipolar disorder episode over the time as well as determining the risk factors affecting bipolar disorder.